The effect of laparoscopic versus robotic low anterior resection of rectum on postoperative pain: A propensity score matching analysis - Hanbyul Lee; Beom Gyu Kim; Yong Gum Park; Hyun Kang (Korean Journal of Clinical Oncology, 2016)
Purpose The aim of this study was to compare postoperative outcomes regarding pain and pain management in patients who underwent robot-assisted low anterior resection (RA-LAR) with laparoscopy-assisted low anterior resection (LA-LAR). Methods Medical records of adult patients who underwent LA-LAR (group L) or RA-LAR (group R) using robotic system (da Vinci Surgical System, Intuitive Surgical Inc., Sunnyvale, CA, USA) were collected prospectively at Chung-Ang University Hospital between January 1, 2010 and December 31, 2015. Patients were matched at a 1 to 1 ratio from Group L and R using propensity score-matching method. Intravenous patient-controlled analgesia (IV-PCA) was applied to the patients postoperatively, and the severity of postoperative pain visual analogue scale (VAS) and nausea as the numerical rating scale (NRS) was evaluated. The incidence of vomiting, dizziness, headache, and PCA clamping was also recorded. Additional fentanyl was administered as a rescue analgesic if the VAS score was over 3, and until VAS was less than 3. Results In the overall series, there was no significant difference between group L and group R regarding pain VAS, nausea NRS, number of vomiting episodes at day 0 and day 1. However, after propensity score analysis, pain VAS and the use of rescue analgesic at day 0 was lower in group L compared to group R (P=0.038, P=0.040). Conclusion In regards to postoperative pain, RA-LAR did not show clear benefit over LA-LAR.